2019
DOI: 10.1093/ofid/ofz302
|View full text |Cite
|
Sign up to set email alerts
|

Blurred Molecular Epidemiological Lines Between the Two Dominant Methicillin-Resistant Staphylococcus aureus Clones

Abstract: Background Methicillin-resistant Staphylococcus aureus (MRSA) causes life-threatening infections in both community and hospital settings and is a leading cause of health care–associated infections (HAIs). We sought to describe the molecular epidemiological landscape of patients with MRSA bloodstream infections (BSIs) at an urban medical center by evaluating the clinical characteristics associated with the two dominant endemic clones. Methods … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 36 publications
3
10
0
Order By: Relevance
“…These rates are much higher than reported mortality rates for patients hospitalized for COVID-19, with rates of up to 25% in patients who were mechanically ventilated [ 4 , 15 , 16 ]. Reported mortality rates for patients with S. aureus bacteremia are up to 30% [ 17–19 ]. As the median days from positive blood culture to death was <8, S. aureus bacteremia was likely to have contributed to the deaths.…”
Section: Discussionmentioning
confidence: 99%
“…These rates are much higher than reported mortality rates for patients hospitalized for COVID-19, with rates of up to 25% in patients who were mechanically ventilated [ 4 , 15 , 16 ]. Reported mortality rates for patients with S. aureus bacteremia are up to 30% [ 17–19 ]. As the median days from positive blood culture to death was <8, S. aureus bacteremia was likely to have contributed to the deaths.…”
Section: Discussionmentioning
confidence: 99%
“…Skin and soft tissue and peripheral intravenous catheter (PIV) infections tended to correlate more frequently to the CC8 MRSA. While CC8 is associated with community skin derived infections [26], we have previously observed that CC8 was also associated with PIV infections [13] highlighting the importance of community clones causing hospital-onset infections.…”
Section: Discussionmentioning
confidence: 96%
“…The CC 5 has historically encompassed hospital-associated genotypes, and the CC8 the community genotypes. As our work [13] and others [14] [15] have found these differences and their correlations are merging, we tested the associations between infection with dominant MRSA genotypes and the salient clinical features for the study population.…”
Section: Introductionmentioning
confidence: 99%
“…Variables were analyzed initially in a univariate logistic regression model. Variables p ≤0.2 were then placed into a stepwise multivariate logistic regression model [17]. An additional in-depth chart review was performed for subjects identified as being involved in transmission events.…”
Section: Methodsmentioning
confidence: 99%